2022
DOI: 10.1186/s41983-022-00445-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline predictors of progression of Parkinson’s disease in a sample of Egyptian patients: clinical and biochemical

Abstract: Background Clinical progression of Parkinson’s disease (PD) is highly heterogeneous, and its predictors are generally lacking. Identifying predictors of early disease progression is important for patients’ management and follow-up. The current study aims to identify clinical, neuroimaging and biochemical baseline predictors of motor progression in patients with PD. Forty-five PD patients were assessed at baseline, 6 months and 1 year using MDS-UPDRS total and subscores, Hoehn and Yahr (H&Y)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…An important observation in this study is that around one quarter of PD patients who did not have the p.Gly2019Ser mutation experienced symptoms before turning 50 years old. This percentage exceeds the global Early Onset Parkinson's Disease (EOPD) rates of 3-14% and aligns closely with data from previous clinical and epidemiological studies on EOPD in Egypt 23,35,36 . Interestingly, the incidence of a family history of PD was relatively low, around 16% in p.Gly2019Ser carriers and 11% in non-carriers.…”
Section: Discussionsupporting
confidence: 87%
“…An important observation in this study is that around one quarter of PD patients who did not have the p.Gly2019Ser mutation experienced symptoms before turning 50 years old. This percentage exceeds the global Early Onset Parkinson's Disease (EOPD) rates of 3-14% and aligns closely with data from previous clinical and epidemiological studies on EOPD in Egypt 23,35,36 . Interestingly, the incidence of a family history of PD was relatively low, around 16% in p.Gly2019Ser carriers and 11% in non-carriers.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies had assessed the total time required to complete the Timed Up and Go (TUG) test and found that more advanced PD stages are associated with an increased time required to perform the test. However, these studies did not account for the HY stages and, therefore, our results are not entirely comparable (Schenkman et al, 2011;Helmy et al, 2022). Nonetheless, although this variable allows for differentiating the stages, clinical information regarding the physiological factors is missing.…”
Section: Discussionmentioning
confidence: 84%
“…However, due to the limited number of studies and inconsistency of results among current studies, no significant conclusions can be drawn. showing non significance due to limited number of studies and inconsistence result among current studies (Helmy et al, 2022). For a significant period of time, the Unified Parkinson's Disease Rating Scale (UPDRS) was the primary means of assessing the progression of PD.…”
Section: Disease Progressionmentioning
confidence: 99%